Transformasi Ilmu Wariga Dalam Masyarakat Adat Buleleng Antara Tradisi Dan Modernitas - Untara, I Made Gami Sandi (Jayapangus Press, 2025)
Wariga is a traditional knowledge system rooted in Balinese Hindu cosmology, transmitted across generations through ritual practice, oral tradition, and classical palm-leaf manuscripts (lontar). It serves as a spiritual and practical guide for determining auspicious (dewasa ayu) and inauspicious (ala dewasa) days for a wide range of activities, including religious ceremonies, agricultural practices, construction, marriage, and travel. In the indigenous communities of Buleleng, Wariga has long functioned as a sacred system sustaining harmony between humans, nature, and the divine. However, the forces of modernity, technological digitization, and generational shifts in values have contributed to significant transformations in the way Wariga is practiced, interpreted, and valued. This study aims to examine how Wariga is transforming in contemporary Buleleng society and to analyze the responses of local communities particularly customary leaders and younger generations to these changes. Employing a qualitative descriptive method, data were collected through participant observation, semi-structured interviews with Wariga experts, community elders, youth, and digital content creators, as well as document and media analysis. The findings reveal a shift from a sacred, community-based epistemology to a more individualized and pragmatic application of Wariga, often accessed via digital platforms and mobile applications. Youth tend to engage with Wariga symbolically and functionally, while many traditional leaders express concern over the erosion of its spiritual and philosophical depth. Despite this, emerging intergenerational initiatives aim to revitalize Wariga through educational, contextual, and culturally grounded digital strategies. The study concludes that Wariga is not disappearing but is undergoing a dynamic reconfiguration shaped by the tension between tradition and modernity.